Legal Protection For Local Communities In Natural Resource Utilization Conflicts: A Literature Review - Dian Wibowo; Harry Sudhana; Hardjito S. Darmojo (International Journal of Education, Vocational and Social Science, 2026)
The escalation of natural resource exploitation often places local communities in a vulnerable position, leading to persistent socio-environmental conflicts. This study aims to analyze the implementation of legal protections for local communities within the context of natural resource utilization and to identify the structural barriers that hinder environmental justice. Using a qualitative descriptive method through a comprehensive documentary study, this research examines various legal frameworks, scholarly discourses, and judicial precedents. The findings reveal a significant "implementation gap" between statutory mandates and grassroots reality. While the law theoretically provides safeguards through mechanisms such as Environmental Impact Assessments (AMDAL) and the recognition of customary rights, these are often undermined by pro-investment policies, such as the Omnibus Law on Job Creation, which simplify licensing at the expense of public participation. Furthermore, bureaucratic hurdles in recognizing indigenous land tenure continue to marginalize local inhabitants. The study concludes that legal protection remains formalistic rather than substantive. To achieve genuine environmental justice, there is an urgent need to strengthen Anti-SLAPP regulations, simplify the recognition of customary forests, and shift the legal paradigm from state-centric developmentalism to a community-centered approach that prioritizes distributive and procedural justice. Keywords: Legal Protection, Local Communities, Natural Resources, Environmental Justice, Conflict Resolution.